Aquisição e desenvolvimento linguísticos: investigação e aplicações – sintaxe de português europeu L2 - Madeira, Ana; Alexandre, Nélia (Revista da Associação Portuguesa de Linguística, 2022)
This paper has two major goals. The first one is to present a summary of some of the studies which have been conducted on the L2 acquisition of syntactic properties in European Portuguese within a generative framework, considering the research questions, the phenomena, and the learner profiles which have been investigated, the methodologies used, and the main conclusions which have been reached by these studies. Building on this summary, our second goal is to identify some of the gaps in the existing research and to propose some ideas for future work.